Changes in histopathology and heteroplasmy rates over 8 years and effectiveness of taurine supplementation in a patient with mitochondrial nephropathy caused by MT-TL1 mutation: A case report - Toshiyuki Imasawa; Hiroshi Kitamura; Takehiko Kawaguchi; Yukiko Yatsuka; Yasushi Okazaki; Kei Murayama (Heliyon, 2023)
The m.3243A > G mutation in the mitochondrially encoded tRNA leucine 1 (MT-TL1) gene is known to cause mitochondrial nephropathy. However, its long-term effects of the m.3243A > G mutation on renal histopathology or heteroplasmy rates remain unknown. Here we present the case of a female patient who underwent renal biopsy at 34 years of age to investigate the reason for a low estimated glomerular filtration rate (eGFR) of 47.9 mL/min/1.73 m2. Light microscopy revealed nephrosclerosis with granular swollen epithelial cells (GSECs) in the renal tubules. Genetic testing revealed the m.3243A > G mutation in the MT-TL1 gene. Over a follow-up period of 8 years, the eGFR declined at a rate of 1.50 mL/min/1.73 m2/year. A second renal biopsy was performed at the age of 42 years; the patient's glomerular sclerosis rate had increased from 45.5% to 63.2%, and the frequency of GSECs in the collecting ducts had increased from 5.8% to 20.8%. Furthermore, the heteroplasmy rate in blood cells and urinary sediment cells increased from 9% to 20% and 20% to 53%, respectively. Taurine therapy was initiated just after the second kidney biopsy. To date, after approximately 3 years of taurine administration, the rate of eGFR decline has markedly decreased to 0.26 mL/min/1.73 m2/year. This experience suggests that an increased heteroplasmy rate may be associated with the progression of mitochondrial nephropathy caused by MT-TL1 mutation. Furthermore, our case is the first to suggest the effectiveness of taurine for mitochondrial nephropathy caused by the m.3243A > G mutation in the MT-TL1 gene.